Kawasaki Disease Presenting with Bloody Diarrhea and Acute Renal Failure: First Case - Saviour, Mary Jacqueline (Pediatr Rep, 2017)
Kawasaki disease (KD) is an acute febrile vasculitis of an unknown cause. It affects children <5 year of age, even if cases over 5 years old have been also reported. It is the commonest cause of acquired heart diseases in children which may lead to serious morbidity and mortality. The complications and mortality increase when the diagnosis is delayed. One of the main reasons leading to delayed diagnosis and consequent delayed treatment is the unusual presentation of KD. Its unusual manifestations have been increasingly reported to jeopardize the timely diagnosis and proper treatment. As there is not yet available blood test to diagnose it, low threshold should be taken into account for considering KD, when the clinical criteria are not typical. KD with renal manifestations is infrequently described. We present and discuss a case of an unusual presentation of KD presenting as bloody diarrhea and acute renal failure.